2022
DOI: 10.3399/bjgp.2021.0547
|View full text |Cite
|
Sign up to set email alerts
|

Association between hip pain and radiographic hip osteoarthritis in primary care: the CHECK cohort

Abstract: Background: The diagnosis of hip osteoarthritis is often based on clinical symptoms, such as pain and stiffness, and radiographic features. However, the association between hip pain and radiographic hip osteoarthritis (ROA) remains uncertain. Aim: To examine the association between hip pain and hip ROA. Design and setting: Cross-sectional analysis of a Dutch cohort, the Cohort Hip and Cohort Knee (CHECK) study. Methods: Participants (45-65 years) experienced hip and/or knee pain for which they had no prior con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Third, we could not evaluate hip pain because of the retrospective study design. Hip pain is a chief symptom of hip OA; however, the precise association between hip OA and pain remains unclear [ 37 40 ], and most individuals with hip pain do not have radiographic hip OA [ 38 , 41 ]. Thus, we believe that the evaluation of hip pain is not relevant to this study.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we could not evaluate hip pain because of the retrospective study design. Hip pain is a chief symptom of hip OA; however, the precise association between hip OA and pain remains unclear [ 37 40 ], and most individuals with hip pain do not have radiographic hip OA [ 38 , 41 ]. Thus, we believe that the evaluation of hip pain is not relevant to this study.…”
Section: Discussionmentioning
confidence: 99%
“…We found female sex to be the only risk factor statistically significantly associated with both incident clinical and radiographic hip OA. This might not be surprising, given the inconsistency in reported cross-sectional associations between hip symptoms and radiographic hip OA [ 3 , 8 , 10 , 19 ] and the low prevalence of radiographic hip OA in patients consulting for hip pain [ 21 ]. Recent systematic reviews showed that hip shape morphologies were strong risk factors for radiographic hip OA but also confirmed a lack of knowledge on the association between hip shape morphologies and clinical definitions of hip OA [ 4 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, startling language and images of “bone-on-bone” disease can have nocebo effects. In fact, there is substantial discordance between radiographic severity and pain experience [38,48], and exercise therapy can be effective, irrespective of radiographic severity [25,32,53]. Effectiveness depends on establishing a dosage of exercise therapy sufficient for strengthening and including neuromuscular training for the modification of aberrant movement patterns.…”
Section: Rehabilitation Considerations: Advanced Hip Osteoarthritismentioning
confidence: 99%